PREPARATION OF ACTIVATED CHARCOAL FROM Terminalia catappa L. SEED SHELL AS AN ADSORBENT OF LIQUID WASTE OF TOFU INDUSTRY - Ola, Pius D.; Bria, Apriance M.; Gauru, Imanuel; Rozari, Philiphi De (Universitas Nusa Cendana, 2023)
A research on preparing activated charcoal from Terminalia catappa L. seed shell has been done. This study aimed to determine the characteristics of activated charcoal from Terminalia catappa L.seed shells and test its ability to reduce COD and TSS from a liquid waste of the tofu industry. The parameters studied in characterizing activated charcoal included moisture content, ash content, absorption of I2 and surface area using methylene blue. Analysis of the COD parameter used the redox titration method, while the TSS parameter used the gravimetric method. he optimum time for applying activated charcoal to liquid tofu waste was by measuring COD and TSS levels after interaction with activated charcoal. Results of activated charcoal characterization showed a moisture content of 5%, ash content of 2.10%, an absorption capacity of I2 761.4 mg/g and a surface area of ​​26.74 m²/g. The highest decrease in COD levels occurred at 90 minutes of contact time from initial levels of 2,976 mg/L to 2,304 mg/L, with a reduction efficiency of 22.6%, and the highest decrease in TSS levels occurred at 90 minutes of contact time from initial levels of 1,440 mg/L to 334 mg/L, with a reduction efficiency of 76.8%. Generally, activated charcoal from Terminalia catappa L. seed shells showed an ability to reduce the COD and TSS from the liquid waste of the tofu industry.